The effects of aerobic exercise and heat stress on the unbound fraction of caffeine - McLaughlin, Mackenzie; Dizon, Kaye; Jacobs, Ira (Frontiers in Physiology, 2025)
IntroductionThe fraction of drug circulating in the blood that is not bound to plasma proteins (fu) is considered pharmacologically active since it readily binds to its receptor. In vitro evidence suggests that changes in temperature and pH affect the affinity of drug binding to plasma proteins, resulting in changes in fu. In light of the well-established effects of exercise on body temperature and blood pH, we investigated whether an increase in blood temperature and decrease in pH facilitated through passive heating and exercise translated to a change in the fu of caffeine.MethodsTen healthy participants (4 females and 6 males; age: 21.9 ± 2.7 years [means ± SD]) ingested 3 mg/kg of anhydrous caffeine on two separate occasions comprised of a control trial involving 105 min of rest, and an experimental trial involving 10 min of passive heating, followed by 20 min of cycling at 55% V˙O2peak, and then 10 sprint intervals at 90% V˙O2peak. Venous blood was sampled and the plasma was processed via ultrafiltration to quantify the fu of caffeine and its major metabolite, paraxanthine.ResultsThe exercise protocol resulted in maximal increases in core temperature of 1.37°C ± 0.27°C and lactate of 10.34 ± 3.33 mmol/L, and a decrease in blood pH of 0.12 ± 0.051 (all p < 0.05), which did not affect the fu of caffeine (baseline: 0.86 vs post-exercise: 0.75; p = 0.30) or paraxanthine (baseline: 0.59 vs. post-exercise: 0.70; p = 0.11). Furthermore, the rate of metabolism of caffeine assessed through the metabolic ratio ([paraxanthine]/[caffeine]) did not differ between resting and exercise trials.DiscussionTherefore, the changes in blood temperature and pH in this study did not affect the fu of caffeine or paraxanthine.